A Cytosolic Bypass and G6P Shunt in Plants Lacking Peroxisomal Hydroxypyruvate Reductase. Issue 2 (18th March 2019) - Li, Jiying; Weraduwage, Sarathi M.; Preiser, Alyssa L.; Tietz, Stefanie; Weise, Sean E.; Strand, Deserah D.; Froehlich, John E.; Kramer, David M.; Hu, Jianping; Sharkey, Thomas D.
Abstract : Triose phosphate isomerase inhibition in plants lacking peroxisomal hydroxypyruvate reductase is overcome by exporting triose phosphate and importing Glc 6 P, but this stimulates a Glc 6 P shunt and cyclic electron flow. Abstract: The oxygenation of ribulose 1, 5-bisphosphate by Rubisco is the first step in photorespiration and reduces the efficiency of photosynthesis in C3 plants. Our recent data indicate that mutants in photorespiration have increased rates of photosynthetic cyclic electron flow around photosystem I. We investigated mutant lines lacking peroxisomal hydroxypyruvate reductase to determine if there are connections between 2-phosphoglycolate accumulation and cyclic electron flow in Arabidopsis ( Arabidopsis thaliana ). We found that 2-phosphoglycolate is a competitive inhibitor of triose phosphate isomerase, an enzyme in the Calvin-Benson cycle that converts glyceraldehyde 3-phosphate to dihydroxyacetone phosphate. This block in metabolism could be overcome if glyceraldehyde 3-phosphate is exported to the cytosol, where cytosolic triose phosphate isomerase could convert it to dihydroxyacetone phosphate. We found evidence that carbon is reimported as glucose-6-phosphate, forming a cytosolic bypass around the block of stromal triose phosphate isomerase. However, this also stimulates a glucose-6-phosphate shunt, which consumes ATP, which can be compensated by higher rates of cyclic electron flow.